Undrained Cyclic Response and Resistance of Saturated Calcareous Sand considering Initial Static Shear Effect. (21st August 2021) - Li, Baojian; Guo, Panpan; Zhou, Gaoyun; Wang, Zhe; Lei, Gang; Gong, Xiaonan
Abstract : Sand elements in the natural or manmade field have often undergone initial static shear stresses before suffering cyclic loading. To explore the effect of static shear stress, a series of undrained cyclic triaxial tests were performed on dense and loose calcareous sand under different initial and cyclic shear stresses. The triaxial test results are used to describe the effect of static shear stress on the cyclic response of the calcareous sand with different relative density. Cyclic mobility, flow deformation, and residual deformation accumulation are the three main failure modes under varying static and cyclic shear stress levels. The cyclic resistance of dense sand is greater than that of loose sand, but the initial static stress has different effects on the cyclic resistance of the two kinds of sand. The dense sand owns a higher cyclic resistance with SSR increasing, while for the loose sand, 0.12 is the critical SSR corresponding to the lowest value of the cyclic resistance. The dense sand has more fast accumulation of dissipated energy, compared with loose sand. Additionally, an exponential relationship is established between static shear stress, relative density, and normalized energy density.